Indra seated on his elephant Airavata in the frieze - Temples of India Project Team (Jio Institute, 2024)
In the frieze (of the ceiling of the Harshnath Temple sanctum) of the drumming and dancing gods, is Indra seated on his elephant Airavata, accompanied by a warrior holding a sword and shield and an apsara. Stella Kramrisch, in her work Hindu Temples (vol-2, plate LXVIII, pg 402-403), describes the spirit of the image as follows: ‘the movement sways and surges to either side of a standing god who holds a long lance and seems to have ushered in before Indra the warrior so that he becomes one of the dancers. Indra, enthroned in a posture of ease, the right hand raised in Abhaya-mudra, grants fearlessness; his left-hand holds the Vajra. Small shapes surround him, Matali, his mahout, and companion spirits, Marut-like. The elephant's trunk and the warrior's legs are interlaced; the warrior's is the largest movement; across the depth of the relief, he steps forward into the line of the celestials. Their dance vibrates, to the stamping of the feet, a suave tremor free from tension.' This image resonates with verse 7 of the Harsha stone inscription of Vigraharaja II which mentions that the Lord Harsha (Shiva) is worshipped on the hill by a joyous divine host, Indra.